2020
DOI: 10.1051/0004-6361/201937025
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguous transient ASASSN-17hx

Abstract: Aims. Some transients, although classified as novae based on their maximum and early decline optical spectra, cast doubts on their true nature and whether nova impostors might exist. Methods. We monitored a candidate nova which displayed a distinctly unusual light curve at maximum and early decline through optical spectroscopy (3000-10000 Å, 500 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Following the conclusion that the WD mass for this type of behavior must be low, in order to produce these fluctuations, this work proceeds to the next model, of an extremely low mass WD of 0.45M⊙ in order to attempt to obtain two observational characteristics. The first is an extremely large ejected mass, not typical of observed nova, and calculated for V612 Sct by Mason et al (2020). The second is an orbital period of order three hours, as deduced for V1391 Cas by Schmidt (2021).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Following the conclusion that the WD mass for this type of behavior must be low, in order to produce these fluctuations, this work proceeds to the next model, of an extremely low mass WD of 0.45M⊙ in order to attempt to obtain two observational characteristics. The first is an extremely large ejected mass, not typical of observed nova, and calculated for V612 Sct by Mason et al (2020). The second is an orbital period of order three hours, as deduced for V1391 Cas by Schmidt (2021).…”
Section: Resultsmentioning
confidence: 54%
“…This conclusion immediately raises the followup question -why are these fluctuations at a plateaued maximum seen in some models and not in others? Mason et al (2020) explain that oscillations are favored in low mass WDs because their gravitational pull is weaker, allowing more time for the expanding envelope to respond to radiative diffusion. This is in addition to the envelope-to-WD mass ratio being orders of magnitude larger for low mass WDs, so mixing takes longer, meaning that the envelope will be less uniform for lower mass WDs.…”
Section: Resultsmentioning
confidence: 98%
“…QU Car has been suggested to belong to the V Sge stars class (Oliveira et al 2014) and to be one of those permanent super soft source binaries that miss detection in the X ray because of high interstellar extinction. HR Del was an extremely slow nova with an anomalous light curve that could result from unstable burning, as proposed for the recent transient ASASSN-17hx (Mason et al 2020), and with a similarly extremely large ejecta mass (9×10 −4 M , Moraes and Diaz 2009). In other words, both objects are neither typical nor representative of their own class, and both could have ongoing burning and, therefore, a completely different WD structure.…”
Section: Discussionmentioning
confidence: 86%
“…References are: (1) Tajitsu et al (2015). Note that they did not correct for the 7 Be decay; (2) Molaro et al (2016), (3) Izzo et al (2018), (4) Tajitsu et al (2016), (5) Selvelli et al (2018), the measurement from Mg absorption is reported, (6) Molaro et al (2020), V612 Sct could be a peculiar object (Mason et al 2020), (7) Arai et al (2021), (8) Izzo et al (2015), the 7 Li abundance is measured from 7 Li 670.8 nm and ionization is estimated with the Na and K lines, the latter is labeled with an asterisk, (9) this paper. material where the 7 Be is observed.…”
Section: Discussionmentioning
confidence: 99%
“…The A( 7 Be) = 𝑙𝑜𝑔𝑁 ( 7 𝐵𝑒)/𝑁 (𝐻𝐼) + 12 abundances of these novae are listed in Tab 4 and shown in Fig 9. So far 7 Be has been found in all the novae where it has been searched off but V612 Sct which has been suggested could be peculiar (Mason et al 2020). By means of a low resolution spectrum of V6595 Sgr taken 91 days after the discovery which shows prominent lines of forbidden Ne and [Ne v] lines, we classified the nova as of ONe type (Williams et al 1991).…”
Section: Be Nova Yieldsmentioning
confidence: 94%